Distortion of Reproductive Justice: Decriminalization of Abortion as a Condition for the Elimination of Social Patriarchy - Fatih Afrisal Bagus Septiano; Satryo Sasono (Jurnal Ilmiah Ilmu Sosial, 2026)
Under Indonesian law, abortion is still classified as an act that is, in principle, prohibited, although exceptions are granted in cases of medical emergencies and pregnancies resulting from rape or other acts of sexual violence. This article employs doctrinal legal research with a critical approach to examine the relationship between criminal norms, health law, service structures, and women’s experiences. The doctrinal approach is used to analyze the construction of abortion prohibitions and exceptions in legislation, while the critical approach is used to assess how these norms operate within a social structure shaped by patriarchy, stigma, and inequalities in access. Using feminist legal theory and a reproductive justice framework, this article demonstrates that the issue of abortion lies not only in the boundaries of legality and illegality but also in women’s ability to access safe, timely, and non-discriminatory services. Poor women, adolescents, survivors of sexual violence, women in underserved areas, and women in vulnerable social positions face distinct challenges in utilizing legal exceptions. The novelty of this article lies in interpreting the decriminalization of abortion as a legal transformation strategy—shifting from a punitive model toward reproductive health protection grounded in bodily autonomy, equitable access, and the state’s tangible, just, and dignified responsibility toward women.